An Investigation of Photoconductivity in Indium Antimonide Crystal - Iltaif, Abdul-Hussain K. (Iraqi Journal of Physics, 2008)
Various Hall Effects have been successfully observed in samples of n-type indium antimonide with values for conductivity, energy gap, Hall mobility and Hall coefficient all agreeing with theory. A particular interest in developing a method for obtaining accurate values of carrier concentrations in semiconductor samples has been fulfilled with an experimental result of (1.6×1016 cm-3 ±10.7%) giving a percentage difference of (6.7%) to a quoted value of (1.5×1016cm-3) at (77K) using an (80mW C.W. CO2) laser beam at (10.6μm) to illuminate a similar sample of n-type indium antimonide, an "Optical" Hall effect has been observed. Although some doubt has been raised as to the validity of effect i.e. "thermal" rather than "Optical", values of (45.8×10-8 seconds) for recombination times of electron, and (3.2×1016cm-3) for the dynamic carrier concentration were calculated by this method. A similar attempt at illuminating the sample with an R.S. catalogue ultra bright L.E.D proved inconsistent with theory and consequent result have been left inconclusive.